2015
DOI: 10.1542/peds.2014-2512
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pneumococcal Vaccination in Pediatric Rheumatology Patients

Abstract: BACKGROUND AND OBJECTIVE: Many pediatric rheumatology patients are at increased risk of pneumococcal disease secondary to a deficient immune system and/or immunosuppressive medications. The goal of this study was to improve pneumococcal vaccination rates in this high-risk population.METHODS: Eligible patients included children at least 2 years old and adults with systemic lupus erythematosus and/or currently on immunosuppressive medication. Interventions included a presentation to rheumatology providers, creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
3
32
0
2
Order By: Relevance
“…Innovative approaches to improve the vaccine uptake have been developed and implemented, including, for example, the use of Electronic Health Record Best Practice Alert or pre-visit and counselling, especially among SLE paediatric patients (78,79). Further initiatives and techniques should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative approaches to improve the vaccine uptake have been developed and implemented, including, for example, the use of Electronic Health Record Best Practice Alert or pre-visit and counselling, especially among SLE paediatric patients (78,79). Further initiatives and techniques should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Having a dedicated nephrology nurse, or vaccine champion, was critical to implement the interventions, as vaccination rates decreased in temporal association with the renal nurse no longer able to focus on this QI initiative. Along with identifying a local vaccine champion, we suggest that the most important additional interventions to increase vaccine rates include obtaining accurate vaccine records from primary care physicians, storing the actual vaccine in the clinic area, and providing at least monthly feedback to providers on the success of the intervention .…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study by Harris et al demonstrated an improvement in pneumococcal vaccination rates among pediatric rheumatology patients using an algorithm and QI process similar to ours. However, combined vaccination rates, defined as having received PCV13 and PPSV23, only increased to 23% by the end of their yearlong QI initiative, and missed opportunities at the visit level were not evaluated . The experience of QI projects focused on PPSV23 administration to high‐risk populations has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Пневмококковая вакцинация существенно снижает частоту инвазивных пневмококковых болезней [23]. Обобщая результаты международных исследований и рекомендаций, можно с уверенностью сделать вывод о положительном эффекте вакцинации против пневмококка у больных сЮИА [23].…”
Section: обсуждение основного результата исследованияunclassified
“…Пневмококковая вакцинация существенно снижает частоту инвазивных пневмококковых болезней [23]. Обобщая результаты международных исследований и рекомендаций, можно с уверенностью сделать вывод о положительном эффекте вакцинации против пневмококка у больных сЮИА [23]. Однако сомнения врачей в безопасности вакцинации пациентов с аутоиммунными заболеваниями, равно как и других больных с иммунодефицитом или получающих иммунодепрессанты, а также отсутствие четкого алгоритма действия в подобных ситуациях приводят к тому, что медицинские работники часто отказываются от вакцинации «сложных» пациентов [24].…”
Section: обсуждение основного результата исследованияunclassified